The relationship between social capital and health in China - Xindong Xue; Erxiao Mo; W. Robert Reed (Kiel Institute for the World Economy (IfW), 2016)
This paper uses the 2005 and 2006 China General Social Survey (CGSS) to study the relationship between social capital and health in China. It is the most comprehensive analysis of this subject to date, both in the sizes of the samples it analyses, in the number of social capital variables it investigates, and in its treatment of endogeneity. The authors identify social trust, social relationships, and social networks as important determinants of self-reported health. The magnitude of the estimated effects are economically important, in some cases being of the same size or larger than the effects associated with age and income. Their findings suggest that there is scope for social capital to be a significant policy tool for improving health outcomes in China.
Keywords: I1; I18; P25; O53; 330; social capital; trust; self-reported health; China; ordered probit regression; heteroskedastic ordered probit regression; interaction effects; endogeneity